Effect of HfB2 and WC additives on the ablation resistance of ZrB2–SiC composite coating manufactured by SPS. Issue 16 (November 2020) - Akbarpour Shalmani, S. Ali; Sobhani, M.; Mirzaee, O.; Zakeri, M.
Abstract: ZrB2 –SiC composite coating with HfB2 -WC as additives was successfully manufactured on graphite substrate by spark plasma sintering method. The effect of HfB2 and WC on coating properties was investigated. The microstructure, phase changes and ablation resistance of the coatings were studied. Results showed that composite coatings with the thickness of 500 μm and penetration depth of 250 μm were obtained for all samples. Results of the oxyacetylene flame test showed that the ablation resistance of the coated graphite was significantly increased. The minimum ablation weight percentage and rate of 2% and 3 mg s −1 were obtained for the composite coating with 3.75% of each additive.